Noncovalent Interaction between Gold Nanoparticles and Multiwalled Carbon Nanotubes via an Intermediatory - Jui-Ming Yeh; Kuan-Yeh Huang; Su-Yin Lin; Yu-Yao Wu; Chao-Chen Huang; Shir-Joe Liou (Journal of Nanotechnology)
A new and effective method has been developed where self-assembled gold nanoparticles (Au-NPs) of ∼10 nm diameter are successfully attached onto the surface of sidewalls and ends of thiol-terminated multi-walled carbon nanotubes (MWNTs) functionalized with orthomercaptoaniline, acting as a bridging agent. It can bridge the carbon nanotubes (CNTs) and Au-NPs via the bi-functional moiety with benzene unit at one end and thiol group at the other end by self-assembly. The ortho-mercaptoaniline was first grafted onto the surface of the CNTs via π-π interaction between the benzene ring of the mercaptoaniline and π-conjugated body of MWNTs surface to produce thiol-terminated CNTs. The bare surface of Au-NPs facilitates to attach on the thiol group of the thiol-terminated CNTs. Attenuated total reflectance FTIR, UV-visible, Raman spectroscopy and X-ray powder diffraction studies were used to verify whether the mercapto-benzene moieties have been attached to the π-conjugated body of functionalized MWNTs. The direct evidence is obtained from transmission electron microscope (TEM) images where self-assembled Au-NPs are attached onto the functionalized MWNTs.